Measurements and CFD modeling of a pulverized coal flame with emphasis on ash deposition. (1st March 2016) - Beckmann, A.M.; Mancini, M.; Weber, R.; Seebold, S.; Müller, M.
Abstract: Measurements of fly ash deposition in a 15 kW pulverized coal jet flame and CFD-based mathematical modeling have been performed. The deposits have been collected at two ports at particle Stokes numbers in the 0.02–0.34 range and particle kinetic energies not larger than 2 × 10 - 9  J. Inertial impaction and thermophoresis have been identified as main mechanisms of particle transport towards the deposition surfaces. Deposition rates on air-cooled probes ( 600 – 700 ° C surface temperature) have been measured to be 24% (Port 2) and 79.4% (Port 3) larger than those measured on uncooled probes ( 1150 ° C surface temperature) due to the enhanced role of thermophoresis. Complex dependencies of the deposition rate on the probe surface temperature and the probe location have been observed. The CFD-model predictions are able to reproduce these dependencies after adjustments to the particle sticking sub-model. The paper contains estimations of both the impaction and sticking efficiencies.